2020
DOI: 10.14295/cs.v11i0.3219
|View full text |Cite
|
Sign up to set email alerts
|

Cymbopogon citratus essential oil has hepato/renal protection and anti-genotoxicity against carbon tetrachloride

Abstract: Nowadays, there is an increasing trend to use aromatherapy for treatment of various diseases. Cymbopogon citratus (Lemongrass) is one of many plants which have been reported to employ successfully in aromatherapy. Herein we decided to explore the protective role of Cymbopogon citratus essential oil (CCEO) against hepato/renal damage and genotoxicity induced by carbon tetrachloride (CCl4) and the relation of this bioactivity with its chemical constituents. Six main groups of mice (five/each) were examined: I- r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The blood biochemical parameters including urea, creatinine, ALT, and AST remained unaffected in all the experimental groups and suggested that Ct is safe at the studied doses . The elevated ALP levels in the arthritic control group might be due to increased bone erosion and activation of lysosomal enzymes .…”
Section: Discussionmentioning
confidence: 81%
“…The blood biochemical parameters including urea, creatinine, ALT, and AST remained unaffected in all the experimental groups and suggested that Ct is safe at the studied doses . The elevated ALP levels in the arthritic control group might be due to increased bone erosion and activation of lysosomal enzymes .…”
Section: Discussionmentioning
confidence: 81%